Blockchain-Based Music Wallet for Copyright Protection in Audio Files - Gürfidan, Remzi (2021)
The works produced within the music industry are presented to their listeners on a digital platform, taking advantage of technology. The problems of the past, such as pirated cassettes and CDs, have left their place to the problem of copyright protection on digital platforms today. Block chain is one of the most reliable and preferred technology in recent times regarding data integrity and data security. In this study, a blockchain-based music wallet model is proposed for safe and legal listening of audio files. The user's selected audio files are converted into block chain structure using different techniques and algorithms and are kept securely in the user's music wallet. In the study, performance comparisons are made with the proposed model application in terms of the length of time an ordinary audio player can add new audio files to the list and the response times of the user. The findings suggest that the proposed model implementation has acceptable differences in performance with an ordinary audio player.